2020
DOI: 10.1186/s40991-020-00047-1
|View full text |Cite
|
Sign up to set email alerts
|

Competition and microfinance institutions’ performance: evidence from India

Abstract: This paper empirically examines whether competition (measured by using the new measure of competition, the Boone Indicator) moderates the relationship between Microfinance Institutions’ (MFIs) social and financial performances using data from 183 Indian MFIs over the period 2005–2014. The findings indicate that MFIs’ social and financial performances have a positive significant relationship. Moreover, the form of the relationship is both lead-lag and cotemporal. The Indian microfinance market was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…The findings, however, did not ascertain the relationship between the IT features and retention of MFIs customers. Wondirad (2020) examined the influence of competition on (MFIs) financial and social performances using 183 Indian MFIs. The findings indicated that competition moderated the social and financial performance of MFIs positively.…”
Section: Marketing Strategies and Mfis Performancementioning
confidence: 99%
See 3 more Smart Citations
“…The findings, however, did not ascertain the relationship between the IT features and retention of MFIs customers. Wondirad (2020) examined the influence of competition on (MFIs) financial and social performances using 183 Indian MFIs. The findings indicated that competition moderated the social and financial performance of MFIs positively.…”
Section: Marketing Strategies and Mfis Performancementioning
confidence: 99%
“…Homaid, Minai and Faaeq (2019) evaluated how marketing orientation influenced the MFIs performance. Wondirad (2020) examined the influence of competition on (MFIs) financial and social performances.…”
Section: Marketing Strategies and Saccos Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In the study conducted by (Ray & Mahapatra, 2019), it was observed that the value of assets of Indian MFIs worsened significantly during 2006-2013 and it negatively impacted the performance. It has also been witnessed that marketed Indian MFIs provide larger loans, than noncommercialized MFIs which strays them from the purpose of financial inclusion (Wondirad, 2020).…”
mentioning
confidence: 99%